The role of NK cells and CD39 in the immunological control of tumor metastases. (3rd June 2019) - Zhang, Haiyan; Vijayan, Dipti; Li, Xian-Yang; Robson, Simon C.; Geetha, Nishamol; Teng, Michele W. L.; Smyth, Mark J.
ABSTRACT: Tumor metastases are responsible for death in the majority of cancer patients. Here we have explored the role of the ectonucleotidase CD39 in select models of tumor metastases and further tested the therapeutic anticancer activity of the NTPDase inhibitor sodium polyoxotungstate (POM-1). CD39 was expressed on tumor-infiltrating regulatory T cells (Treg), myeloid cells and some NK cells, and it was upregulated on these cells within tumors early after inoculation in vivo. NK cell numbers and effector functions were increased in globally CD39-deficient mice and also in WT mice treated with POM-1. Dosing with POM-1 suppressed experimental and spontaneous metastases in four different tumor models and was well tolerated. This anti-metastatic activity was completely abrogated in mice, that were depleted of NK cells, had IFNγ neutralized or were deficient in CD39 expression in bone marrow-derived cells. POM-1 was highly effective in suppressing metastases when used in combination with BRAFi/MEKi or anti-PD-1/anti-CTLA-4 or IL-2. These data highlight the importance of the CD39 pathway in suppressing NK cell-mediated anti-tumor immunity and validate further the development of CD39-based therapies in the clinic.